Penentuan Situs Asam Bronsted-Lewis dari ZSM-5 yang Disintesis Menggunakan Silika Amorphous dari Fly Ash Sawit - Halida Sophia; Muhdarina Muhdarina; Emrizal Mahadin T; Dhea Ardelia E (Sistem Informasi, 2022)
Fly ash is one of the byproducts of palm oil mill. The silica extracted from fly ash can be utilized for the synthesis of ZSM-5 by hydrothermal methods after fusion pre-treatment with NaOH. This study aimed to obtain ZSM-5 and determine the characteristic of the synthesized ZSM-5. The synthesis was performed at various composition molar ratio of SiO2/Al2O3 with addition of PEG-400 as template on temperature 100°C during hydrothermal process. The analysis using XRD showed that the two of three synthesized zeolites were ZSM-5 with crystallinity 67.63% and 28.53%. Analysis using FTIR spectroscopy on synthesized ZSM-5 detected many groups including T-OH hydroxyl groups (Si-OH/Al-OH), TO groups (O-Si-O/O-Al-O) and pentasil groups are typical of ZSM-5. From analysis using pyridine adsorption, it can be concluded that the increases ratio of SiO2/Al2O3 causes the number total acid side of the sample increased.